2013
DOI: 10.1021/bi401433f
|View full text |Cite
|
Sign up to set email alerts
|

A Lys–Trp Cation−π Interaction Mediates the Dimerization and Function of the Chloride Intracellular Channel Protein 1 Transmembrane Domain

Abstract: Chloride intracellular channel protein 1 (CLIC1) is a dual-state protein that can exist either as a soluble monomer or in an integral membrane form. The oligomerization of the transmembrane domain (TMD) remains speculative despite it being implicated in pore formation. The extent to which electrostatic and van der Waals interactions drive folding and association of the dimorphic TMD is unknown and is complicated by the requirement of interactions favorable in both aqueous and membrane environments. Here we rep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
20
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(21 citation statements)
references
References 57 publications
(115 reference statements)
1
20
0
Order By: Relevance
“…In response to increased cytoplasmic oxidation or pH changes, cytoplasmic soluble CLIC proteins insert into cellular membranes where they act as anion channels that counteract cationic fluctuations. CLIC proteins participate in a number of biological functions, including regulation of membrane potential, cell volume regulation, cell proliferation and apoptosis [26][27][28][29]. Upon phagocytosis, CLIC1 has been shown to translocate into the phagosomal membrane where it colocalizes with NADH oxidase and modulates phagosomal acidification.…”
Section: Introductionmentioning
confidence: 99%
“…In response to increased cytoplasmic oxidation or pH changes, cytoplasmic soluble CLIC proteins insert into cellular membranes where they act as anion channels that counteract cationic fluctuations. CLIC proteins participate in a number of biological functions, including regulation of membrane potential, cell volume regulation, cell proliferation and apoptosis [26][27][28][29]. Upon phagocytosis, CLIC1 has been shown to translocate into the phagosomal membrane where it colocalizes with NADH oxidase and modulates phagosomal acidification.…”
Section: Introductionmentioning
confidence: 99%
“…In contrast, the polypeptides of MCA1 and MCA2 have a single transmembrane segment, as shown in this study, and assemble as a homotetramer to form a Ca 2ϩ -permeable channel (14,42). Chloride intracellular channels (CLICs) in mammals may have a single N-terminal transmembrane segment, but the number of subunits has not yet been established (43)(44)(45)(46). In this context, MCA1 and MCA2 are structurally unique among MS channels, and thus, elucidation of the molecular mechanisms of MCA1 and MCA2 involved in sensing mechanical stresses, including hypo-osmotic stress and membrane stretch, and in permeating Ca 2ϩ is important.…”
Section: Discussionmentioning
confidence: 79%
“…Thereby, a cationformation in solution is characterized by a small red shift of a few nanometers, accompanied by an increase in fluorescence intensity of about 30 -40% (38,39). However, in contrast to spectra of proteins in solution, Peter et al (40) reported even small blue shifts for a peptide embedded in different membrane mimetics. Comparing the fluorescence spectra of the WT and the R735L mutant of yeast V-ATPase, we observed the expected intensity increase of ϳ30% (max of 339.81 Ϯ 1.40 nm for the WT and 341.66 Ϯ 2.03 nm for R735L) ( Fig.…”
Section: A Cation-interaction Facilitates Proton Transportmentioning
confidence: 99%